Mislabeling in Indian Branded Health Foods: Case Study with Immunity Booster Food and Protein Supplement - Jhinuk Gupta; Shreya P Sarathy; Tharani Lakshmi Tharuni; Amrita Shaw (International Journal of Nutritions, 2024)
One of the most recent risks to livelihood security is food "mislabeling". Mislabeling occurs when the label on the packaging does not convey the true character of the product with respect to quality, components, nutritional values and health advantages. Mislabeling includes modifying the original recipe, substituting a component, omitting required warning words, and concealing the presence of certain potentially dangerous ingredients. Purposeful mislabeling is done for financial advantage, whereas inadvertent mislabeling occurs when food manufacturers lack awareness of food safety regulations. Mislabeling can happen with any packaged food product. Unfortunately, health foods are also not out of the grip of mislabeling. “Health food” refers to any food that is touted as being extremely beneficial to one’s health. The health food market is one of the fastest expanding markets globally, especially after COVID-19 pandemic. The two most popular goods in this category are protein supplements and immunity booster food supplements. Here we report nutritive assessments of four protein supplements and five immunity booster food supplements which are popular in the Indian market and contain improper labeling. In order to assess the scope of mislabeling in these products, protein supplements were tested for their protein, fat and total carbohydrate content and the immunity booster food supplements were analytically tested for vitamin C and zinc content and antioxidant activity. Notable disparities, as high as 1900%, were found between the printed value and the estimated value of certain nutrients. This clearly shows the prevalence of mislabeling in Indian health food sector and underscores the importance for stringent labeling regulation and implementation.
Keywords: Food safety; health supplements; immunity booster; mislabeling; protein powder; quantitative study